Entrepreneurship in secondary and tertiary sectors: The same determinants? - Gonçalo Rodrigues Brás (Taylor & Francis Group, 2020)
The aim of this study is to test empirically the determinants of entrepreneurship (overall and sectoral) in the Portuguese economy. Despite the methodological limitations inherent in such studies, which are mainly due to the incompatibility of some series and the temporal limitations of some data, this challenge is fuelled by the novelty of a cross-sectoral view of the entrepreneurial phenomenon. For this purpose, we employ an estimation approach based on time-series models to confirm (or reject) diverse hypotheses. The main results indicate that the determinants of entrepreneurship in the industry are significantly different from the determinants of entrepreneurship in the services sector in Portugal. On the other hand, the determinants of entrepreneurship in the service sector are very similar to those explaining the overall entrepreneurial activity, due to the high share of services in the total economic activity. The main conclusions of the study can guide institutional decision-makers to adopt adequate policies for promoting entrepreneurship in Portugal. Additionally, strategic routes are suggested for the sustainable development of entrepreneurial activity.